Germinación y calidad de plantas de Iryanthera tricornis Ducke "cumala colorada" con diferentes sustratos y porcentajes de iluminación en el laboratorio de producción y adaptación de plantas del CIEFOR - Puerto Almendra, Loreto-Perú. 2020 - Saboya Lancha, Cynthia Paola (2021)
The experiment was carried out at the CIEFOR Puerto Almendra FCF - UNAP nursery, San Juan Bautista, Maynas, Loreto. Objective, to determine the increase in height and diameter; survival and quality of 200 seeds of Iryanthera tricornis Ducke in nursery with different substrates. The planting beds were prepared at ground level, with material from the area; The simple randomized experimental design with 2 factors was used, with 8 treatments and 25 repetitions. The greatest increase in height in the BII treatment (Black earth + chicken manure / Lighting at 60%) with 8.0 cm at the end of the experiment; while the greatest increase in the diameter of the seedlings was registered in the BII treatment (Black earth + chicken manure / Lighting at 60%) with 0.35 mm. The seedlings of Iryanthera tricornis Ducke "cumala colorada" registered results between 50% and 59% survival for treatments. The highest amount of survival with 24 live plants (96%) was found in the BII treatment (Black earth + chicken manure / Lighting at 60%). Use substrates that correspond to the BII treatment (black earth + chicken manure / 60% illumination) and DII (black earth + rotten stick / 60% illumination) to achieve the best results in the experiment.